Behavioral and Subjective Performance with Digital CROS/BiCROS Hearing Instruments. - Schafer, Erin C.; Baldus, Nicole; D'Souza, Miranda; Algier, Katherine; Whiteley, Paige; Hill, Margaret (Journal of the Academy of Rehabilitative Audiology, 2013)
The efficacy of wireless digital CROS and BiCROS hearing instruments was determined for 12 adults with single-sided deafness (SSD) and 12 adults with asymmetrical hearing loss. Participants’ speech-recognition performance in noise (with a loudspeaker arrangement that was disadvantageous) significantly improved when using the CROS/BiCROS devices as compared to the unaided condition. Ratings on three subjective questionnaires yielded positive average CROS/BiCROS ratings from the participants in this study. Given the results of the present study and results from previous investigations, these instruments may be considered on a trial basis for individuals with SSD or asymmetrical hearing loss.